2012
DOI: 10.1021/cr2004822
|View full text |Cite
|
Sign up to set email alerts
|

2-Azabicyclo[2.2.1]hept-5-en-3-one: Chemical Profile of a Versatile Synthetic Building Block and its Impact on the Development of Therapeutics

Abstract: | Chem. Rev. 2012, 112, 4642−4686 4.4.3. Enantioselective Synthesis of Various Heterocyclic Compounds via ROM-RCM Domino Metathesis of Ring-Opened Vince Lactam Derivatives 4669 4.5. Use of Vince Lactam as a Standard in Chemical Analysis of Compounds and Optical Activity of Stereoisomers 4669 5. Conclusions 4669 Author Information 4669 Corresponding Author 4669 Notes 4669 Biographies 4670 Acknowledgments 4670 Abbreviations 4670 References 4671V). The well-known preference of the hydrolase enzymes to attack a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 917 publications
0
79
0
1
Order By: Relevance
“…ABH has been used for the synthesis of carbocyclic nucleosides for more than 30 years, since Robert Vince recognised the potential of this intermediate to synthesise carbocyclic nucleosides with the required cis orientation of both hydroxymethyl and nucleobase groups. A recent review collected the different synthesis and numerous applications of ABH (Singh and Vince, 2012). Enzymatic resolution of ABH has been extensively studied, and there are several enzymes that provide excellent enantioselectivity and facilitate the preparation of enantiopure carbocyclic nucleosides.…”
Section: As Nucleoside Prodrugsmentioning
confidence: 99%
“…ABH has been used for the synthesis of carbocyclic nucleosides for more than 30 years, since Robert Vince recognised the potential of this intermediate to synthesise carbocyclic nucleosides with the required cis orientation of both hydroxymethyl and nucleobase groups. A recent review collected the different synthesis and numerous applications of ABH (Singh and Vince, 2012). Enzymatic resolution of ABH has been extensively studied, and there are several enzymes that provide excellent enantioselectivity and facilitate the preparation of enantiopure carbocyclic nucleosides.…”
Section: As Nucleoside Prodrugsmentioning
confidence: 99%
“…Thus, much effort has been made to construct specific enzymes from promiscuous enzymes (Yoshikuni et al 2006). Chiral bicyclic γ-lactam, 2-azabicyclo[2.2.1]hept-5-en-3-one, is an important building block for the synthesis of a series of chemotherapeutic agents that are used as cardiac vasodilators and antiviral drugs (Singh and Vince 2012). Kinetic resolution of racemic γ-lactam by γ-lactamase is a powerful method for producing chiral γ-lactam (Wang et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Mhg, a (Ϫ)-␥-lactamase with high stability and enantioselectivity, was first isolated and purified from Microbacterium hydrocarbonoxydans (13). Mhg can be utilized to prepare chiral ␥-lactam (14), which is an important chiral intermediate for the synthesis of a series of antiviral drugs, such as abacavir (targeting HIV) and peramivir (targeting hepatitis and pandemic influenza viruses). Recently, by performing structure similarity analysis combined with classical enzyme assays, we have found that Mhg has perhydrolase activity ( Fig.…”
mentioning
confidence: 99%